المعايير التشخيصية لالتهاب الزائدة الحاد عند الأطفال - ناصر, محمد; مسعود, سجيع; سلهب, نبيلة (Latakia University Journal -Medical Sciences Series, 2018)
تأتي اهمية البحث بالتأكيد على اهم الأعراض والعلامات لالتهاب الزائدة والتشخيص في الوقت المناسب لتجنب المضاعفات والوفيات. الهدف من البحث وضع معايير تشخيصية لالتهاب الزائدة الحاد عند الأطفال على ضوء المعطيات التي حصلناعليها من دراسة عدد أكبر من المرضى بالتهاب الزائدة وتحديد الاستطباب الجراحي للتقليل من المضاعفات وحالات فتح البطن السلبي وإدراج المعايير المدروسة في ميزان خاص يعتمد في مشافينا لتقييم الأطفال بشك التهاب زائدة حاد والاعتماد على هذا الميزان في التدبير . شملت الدراسة104 من الأطفال المراجعين لقسم إسعاف الأطفال في مشفيي الأسد الجامعي و تشرين الجامعي بشكوى ألم بطني مع شك التهاب زائدة حاد ما بين عام 2014_2016 والذين كانت أعمارهم دون 12 سنة .عدد المرضى الذكور 76 مريضا والإناث 28 مريضة ,الألم البطني موجود عند كل المرضى , تم دراسة المعايير التالية(الألم البطني,الإيلام البطني ,الإيلام المرتد,الايكو,البروتين الارتكاسي,الكريات البيض,انحراف الصيغة للأيسر , الحرارة) اتم دراسة هذه المعاييرعند هذه الشريحة لتشخيص أو نفي التهاب الزائدة الحاد ووضعها في ميزان خاص يصلح للاستخدام في تشخيص أو نفي التهاب الزائدة الحاد . وبمقارنته مع المعايير العالمية لاحظنا أن الميزان المدروس في دراستنا أكثر موضوعية ويلغي العامل الشخصي في تشخيص التهاب الزائدة The objective of this research is to insist on the most important symptoms and signs of appendicitis and diagnosis in a timely manner to avoid complications and deaths. The aim of the study was to establish diagnostic criteria for acute appendicitis in children in the light of the data obtained from the study of a large number of patients with appendicitis and to determine the surgical indication to reduce complications and negative abdominal opening and to include the studied criteria in a spec ial scale in our patients to evaluate children with acute appendicitis depending On this scale. The study included 104 children who visited the Pediatric emergency department at Al-Assad University and University Hospital and Tishreen university Hospital with a complaint of abdominal pain between 2014 and 2016. The number of male patients was 76 patients and 28 females, abdominal pain was present in all patients, The following criteria were studied (abdominal pain, abdominal tenderness, rebound tenderness, ultra sound, leukocytosis, shift to left, fever,crp). These criteria were studied to diagnose acute appendicitis and to put them in a special scale for use in diagnosis or denial acute appendicitis. In comparison with international standards, we observed that the scale studied in our study is more objective and eliminates the subjective factor in the diagnosis of appendicitis.